ALGORITHMIC SUPPORT FOR PRE-PROCESSING DEVICES SPECTROMETRIC SIGNALS - Djurabayeva Feruza Baxtiyarovna, Abidova Gulmira Shuxratovna, Mirsagdiyev Orifjon Alimovich (Journal Park Publishing, 2022)
In systems intended for preliminary processing of spectrometric information, when implementing spectrometric analytical methods, due to the complexity of processing tasks, they have a two or even three-level structure. At the lower level of the system for preliminary processing of spectrometric signals, there are means for converting analytical spectrometric signals and their preliminary processing (smoothing, filtering), at the upper level - computer tools for complex processing of analytical spectrometric information (linearization of the characteristics of analytical spectrometric instruments, approximation of discrete values of an analytical spectrometric signal , compression of analytical spectrometric data, determination of the intensities of analytical peaks at the output of spectrometric equipment, separation of combined peaks, identification of components of analytes, control of the process of analytical spectrometric measurements, etc.). To determine the tasks to be performed at each level, an algorithm of tasks to be performed is used. This article presents the algorithmic support of devices for pre-processing of spectrometric signals, on the basis of which each process can be distributed over certain levels.
Keywords: spectrometry, devices for preliminary processing of information, analog-digital converters.